The : A travel cost method estimation of demand for two destination salmon rivers in Ireland - Gianluca Grilli; Gavin Landgraf; John Curtis; Stephen Hynes (The Economic and Social Research Institute (ESRI), 2017)
In this paper we use the travel cost method to estimate the demand function for two of western Ireland's destination salmon fisheries: the River Moy in County Mayo and the River Corrib in County Galway. Data were collected by an on-site survey questionnaire and demand was estimated using count data models. In the study sites commercial fishing was banned to avoid unsustainable harvesting of salmon, which removed an important source of income for the local communities. Therefore, the study is important to highlight whether recreational fishing presents an opportunity for further development of the local economy. Welfare estimates from our models indicate that anglers are willing to pay exteuro867 for a day of angling on the Galway and Moy fisheries, approximately double the costs incurred. Differently from previous research, tourists anglers were found to be price sensitive, with a price elasticity close to unity. This means that escalating costs likely result in declining demand among tourist anglers. Corrib and Moy fisheries support local economic activity with visiting anglers' expenditure contributing exteuro22- exteuro31 per angler per day to local incomes, which is an indication of the potential of the fishery resource for economic development.
Keywords: 330